Clima organizacional y satisfacción laboral del personal de serenazgo en la Municipalidad Distrital de Guadalupe, 2021 - Ríos Gamarra, Cindy Estefany (2022)
The thesis was developed with the objective of studying the relationship between the organizational climate and the job satisfaction of serenity employees in the municipality of the district of Guadalupe, 2021. The applied research work was proposed considering the descriptive model, the sample consisted of 42 soldiers from the Serenazgo of the municipality of the district of Guadalupe, who worked with methods and quantitative research methods (statistical method and as a method).) virtual survey) and qualitative research (inductive-deductive method) and finally as a method the virtual interview. From the results obtained, it was possible to point out that the working and communication conditions Therefore, it is important to know the organizational climate and the job satisfaction of its employees, which allows them to make an analysis of the results based on this study. Finally, from the perspective of social work, it was considered that the Municipality should increase programs that help improve and thus all the staff work as a team. This thesis presents the problematic reality of serenity personnel, leadership, interpersonal relationships, communication, and thus facilitating tools for teamwork.